Effects of Discussion-Based Legality-Focused Nursing Record Education on Nursing Students' Knowledge, Self-Confidence, and Nursing Record Performance. - Dohye Kim; Kyoungrim Kang; Jeongyeong Jeon (Journal of Korean Academy of Fundamentals of Nursing, 2025)
Purpose: This study investigated the effects of legality-focused nursing record education for nursing students on their knowledge, self-confidence, and nursing record performance. Methods: A randomized comparison of pre-and post-test results was conducted, with 62 participants from six colleges or universities assigned to either an intervention group (n=31 in three clusters) or a control group (n=31 in three clusters). The experimental group received two 2-hour sessions of legality-focused nursing education through discussions, whereas the control group was provided written handouts. Data collected included measures of knowledge, self-confidence, and nursing record performance. The data were statistically analyzed using SPSS 28.0, with the χ² test, independent t-test, paired t-test, and analysis of covariance. Results: The knowledge and self-confidence scores of both groups improved significantly after the educational intervention. The nursing record performance score improved more in the experimental than in the control group. Conclusion: Universities can apply standardized nursing record education focusing on legal issues by selecting methods appropriate to their curriculum or situation. Education on the legal aspects of nursing records can assist in the utilization of standardized nursing records in clinical practice. Improving the quality of nursing records, in turn, can enhance efficiency among healthcare professionals and contribute to better patient health outcomes.